An investigation into the effects of thermal errors of a machine tool on the dimensional accuracy of parts - Lu, Yuxia (Curtin University, 2012)
The reduction of machining errors has become increasingly important in modern manufacturing in order to obtain the required quality of parts. Geometric error makes up the basic part of the inaccuracy of the machine tool at the cold stage; however, as the machine running time increases, thermally-induced errors start to play a major role in machined workpiece accuracy. Dimensional accuracy of machined parts could be affected by several factors, such as the machine tool’s condition, the workpiece material, machining procedures and the operator’s skill. Of these, the machine condition plays an important role in determining the machine’s performance and its effects on the final dimensions of machined parts. The machine’s condition can be evaluated by its errors which include the machine’s built-in geometric and kinematic error, thermal error, cutting force-induced error and other errors.This research represents a detailed study of the effects of thermal errors of a machine tool on the dimensional accuracy of the parts produced on it. A new model has been developed for the prediction of thermally-induced errors of a three-axis machine tool. By applying the proposed model to real machining examples, the dimensional accuracy of machined parts was improved. The research work presented in this thesis has the following four unique characteristics:• Investigated the thermal effects on the dimensional accuracy of machined parts by machining several components at different thermal conditions of a machine tool to establish a direct relationship between the dimensional accuracy of machined parts and the machine tool’s thermal status.• Developed a new model for calculating thermally-induced volumetric error where the three axial positioning errors were modelled as functions of ball screw nut temperature and travel distance. The influences of the other 18 error components were ignored due to their insignificant influence.• Employed a Laser Doppler Displacement Meter (LDDM) with three thermocouples, instead of the expensive laser interferometer and the large number of thermocouples required by the traditional model, to assess the thermally-induced volumetric errors of a three-axis CNC machining centre. The thermally-induced volumetric error predictions were in good agreement with the measured results.• Applied the newly developed thermally-induced volumetric error compensation model for drilling operations to improve the positioning accuracy of drilled holes. The results show that positioning accuracy of the drilled holes was improved significantly after compensation. The absolute reduction of the positioning errors of drilled holes was an average 30.44 μm at the thermal stable stage, while the average relative reduction ratio of these errors was 77%.Therefore, the proposed thermally-induced volumetric error compensation model can bean effective tool for enhancing the machining accuracy of existing machine tools used in the industry.